Novel antibacterial polyurethane and cellulose acetate mixed matrix membrane modified with functionalized TiO2 nanoparticles for water treatment applications. (August 2022) - Ahmad, Adnan; Sabir, Aneela; Iqbal, Sadia Sagar; Felemban, Bassem F.; Riaz, Tabinda; Bahadar, Ali; Hossain, Nazia; Khan, Rafi Ullah; Inam, Fawad
Abstract: Bacterial contamination is one of the leading causes of water pollution. Antibacterial polyurethane/cellulose acetate membranes modified by functionalized TiO2 nanoparticles were processed and studied. TiO2 nanoparticles were prepared and ultraviolet (UV) irradiated to activate their photocatalytic activity against Escherichia coli ( E. Coil) and Methicillin-resistant Staphylococcus aureus (MRSA) bacteria. Functionalized TiO2 nanoparticles were incorporated in flat-sheet mixed matrix membranes (MMMs). These membranes were characterized for their different properties such as morphology, thermal stability, mechanical strength, surface wettability, water retention, salt rejection, water flux, and their antibacterial performance against E. Coil and MRSA was also tested. The activity of nanoparticles against MRSA and E. coli was analyzed using three different concentrations, 0.5 wt%, 1.0 wt% and 1.5 wt% of nanoparticles and 0.5 wt% of TiO2 nanoparticles showed maximum growth of bacteria. The maximum inhibition was observed in membranes with maximum nanoparticles when compared with other membranes. All these characteristics were strongly affected by increasing the concentration of TiO2 nanoparticles in the prepared membranes and the duration of their UV exposure. Hence, it was proved from this analysis that these TiO2 modified membranes exhibit substantial antibacterial properties. The results are supporting the utilization of these materials for water purification purposes. Graphical abstract: Image 1 Highlights: Application of polyurethane/cellulose acetate membranes modified by functionalized TiO2 nanoparticles E. Coil and MRSA bacteria inhibition. Comprehensive characterizations of functionalized TiO2 nanoparticles incorporation in flat-sheet mixed matrix membranes. Maximum growth of bacteria growth at 0.5 wt% of TiO2 nanoparticles loading.